PERUBAHAN PERILAKU NEGATIF SISWA MELALUI PENERAPAN TEAM GAME TOURNAMENT (TGT) PADA MATERI AKHLAK TERPUJI DI KELAS VIII MTS AL-MUNAWWAROH - KAB. MALANG - SITI UMI RUJIKA; ALI RIF'AN (Piwulang: Jurnal Pendidikan Agama Islam, 2019)
The use of methods that are not in accordance with the purpose of teaching will be an obstacle in achieving the objectives that have been formulated. This study is to find out the changes in students' negative behavior through the application of cooperative methods team games tournament (TGT) models on the material of commendable morals to class VIII students at MTs Al-Munawwaroh - Kab. Poor. This research is a classroom action research that begins pre-cycle and is carried out with 2 (two) cycles. The research subjects were 26 students. The results showed that the TGT method in Aqidah Akhlak subjects was able to change students' negative behavior. This can be seen from the comparison starting from the pre-cycle to the second cycle, namely leaving the class without permission decreasing from 11.5% to 0%, often permission to go to the toilet when learning decreased from 31% to 8%, late entry decreased from 19% to 4%, annoying friends when learning decreases from 11.5% to 0%.